The future of opposition in Turkey: Overcoming identity politics is the key for success - Salim Çevik (Stiftung Wissenschaft und Politik (SWP), 2018)
Muharrem Ince was the presidential candidate of the Republican People's Party (CHP). The election results did not reflect the hopes Ince had created, and his ineptitude in managing the post-election process further undermined his popularity and credibility. However, Ince's inclusive appeals throughout the campaign suggest a potentially successful approach for opposition parties in general and the CHP in particular. To challenge President Erdogan effectively, they need to mitigate the significance of identity politics.
Keywords: 320